أثر تطبيق أنظمة إدارة الجودة على تطور جودة العملية التعليمية خلال الفترة 2009-2017 في كلية الزراعة – جامعة تشرين - طويل, علاء; غانم, غدير (Latakia University Journal -Biological Sciences Series, 2018)
هدف البحث إلى التعرف على واقع تطبيق انظمة إدارة الجودة بكلية الزراعة – جامعة تشرين ومعرفة تأثيراتها على تطور جودة العملية التعليمية خلال الفترة الواقعة بين (2009-2017). وقد تم استخدام منهجية التحليل الكمي بالاستناد على بيانات تم جمعها من سجلات الجامعة. وكان من أبرز النتائج التي تم التوصل اليها، ازدياد أعداد الطلاب بحوالي ثلاثة أضعاف، في حين بقيت قاعات التدريس، ومخابر التدريب، والكادر التدريسي ثابتةً نسبياً، حيث ارتفعت الواجبات التعليمية لعضو الهيئة التدريسية من تدريس 5.4 طالباً في 2009 إلى 14.8 طالب في العام 2017، وتضاعف عمل عضو الهيئة التدريسية بمعدل 2.74 مرة، كما انخفضت حصة الطلاب من المقاعد الدراسية من 1.2 مقعد/طالب إلى 0.41 مقعد لكل طالب في الفترة المدروسة، مما يدلُ على أن أنظمة إدارة الجودة المطبقة في الكلية ليست فعالة بما يكفي كي تنعكس إيجاباً على العملية التعليمية. The goal of this research is to investigat the current application of quality management systems at the faculty of agriculture, Tishreen University and to know the development trends of the educational quality process during 2009-2017. Quantitative analysis methodology, based on data, obtained from university records for the period 2010 to 2016-2017 was used. One of the most important results was the increasing of students number by three times. While the numbers of teaching rooms, training laboratories and teaching staff remained relatively stable. Staff teaching duties were increased from 5.4 students in 2009 to 14.8 in 2017 per member. The duties of teaching member were increased by 2.74 times and the student share of the seats has decreased from 1.2 to 0.41 seats per student during the study period. All figures mentioned affects the quality level of graduates, and indicates that the quality management systems are not effective enough to make the teaching process positive.